Dust at the Cosmic Dawn - Yuri A. Shchekinov; Biman B. Nath (Galaxies, 2025)
Observations provided by the Hubble Space Telescope (HST) and James Webb Space Telescope (JWST) have revealed a surprising abundance of galaxies at the “cosmic dawn” epoch, <semantics>z>7</semantics>. Some of them are found even in a more distant universe at z ≃ 14–16. Most of these galaxies appear to be intriguing: they are found to be either super-bright in the rest-frame ultraviolet (UV) band or super-dusty with a heavily reddened stellar population. The transition from the super-bright and super-dusty regimes seems to occur in the redshift range from z∼10.5 to z∼9.5 within a time range of ∼50 Myr. If confirmed, then the origin of this transition is far from being clear. In the review, we discuss possible mechanisms that can make <semantics>z>10</semantics> galaxies free of dust and also explain the origin of apparently excessive dust in galaxies at intermediate and lower redshifts <semantics>z<10</semantics>.